A comprehensive evaluation of physical and environmental performances for wet-white leather manufacture. (15th December 2016) - Shi, Jiabo; Puig, Rita; Sang, Jun; Lin, Wei
Abstract: This paper presents the comprehensive evaluation results of physical and environmental performances for a novel wet-white (chrome-free) leather manufacturing. The tanning process is optimized as 15 wt% tannic acid (TA) combination with 4 wt% Laponite nanoclay, giving the leather with shrinkage temperature ( T s ) above 86 °C. Inductively coupled plasma-atomic emission spectrometry (ICP-AES) measurements indicate that Laponite can be evenly and tightly bound within the leather matrix, which is further confirmed by scanning electron microscopy and energy dispersive X-ray (SEM-EDX) spectroscopy analysis. The resultant wet-white leathers have reasonable good physical properties that can meet the standard requirements for furniture leather without containing hazardous Cr(VI) and formaldehyde. Further life cycle assessment (LCA) studies shows that tanning process is the main contributor to environmental impact categories in the wet-white tanning process, and tannic acid is the most significant substance factor. Compared to conventional chrome tanning, the wet-white tanning process exhibits much lower abiotic depletion potential (ADP), and reduced global warming potential (GWP) and human toxicity potential (HTP) impacts due to the nature of vegetable tanning; whereas, GWP excluding biogenic carbon and energy consumption are higher owing to prolonged run time. Highlights: Environmentally friendly tanning materials have been exploited in the novel wet-white tanning. Laponite nanoclay can be evenly distributed within leather matrix. The resultant wet-white leather is free of restricted hazardous, Cr(VI) and formaldehyde. The wet-white tanning process does not show absolute advantages in all the environmental impacts from LCA perspective.